Gender differences in electrophysiological characteristics of idiopathic ventricular tachycardia originating from right ventricular outflow tract - Yang, S-G; Mlček, M; Kittnar, O (Physiological research, 2014)
It has become increasingly apparent in recent years that there are important differences of many cardiovascular disorders including ventricular tachycardias in men and women. Nevertheless, so far just few studies have addressed possible gender differences in electrophysiological characteristics of idiopathic ventricular tachycardia from right ventricular outflow tract (RVOT-VT), other than epidemiological ones. This study explored possible gender differences in electrophysiological characteristics and catheter ablation outcome in RVOT-VT patients. Ninety-three patients (mean age 38.7+/-15.5 years, 30 males) with idiopathic RVOT-VT were enrolled and analyzed in our study. Male patients had longer QRS width (99.9+/-19.4 ms vs. 88.4+/-20.7 ms, p=0.02). Female patients had lower right ventricular mean voltage (3.0+/-0.7 mV vs. 3.7+/-0.9 mV, p=0.03), and more low voltage zone over the right ventricular outflow tract free wall (27.0 % vs. 6.7 %, p=0.02). Eighty-one patients passed catheter ablation (23 males). The acute success rate, repeated catheter ablation rate and VT recurrence rate were similar in both genders. The present study provides evidence of the gender differences in electrophysiological findings in patients with idiopathic RVOT-VT. Studies on gender-specific differences in arrhythmia could lead to a better understanding of its mechanism(s) and provide valuable information for the development of optimal treatment strategies.
Keywords: echokardiografie; dospělí; Female; Heart Ventricles; Adult; Tachycardia, Ventricular; výsledek terapie; mladý dospělý; ženské pohlaví; srdeční komory; Catheter Ablation; lidé; katetrizační ablace; Treatment Outcome; Echocardiography; Electrocardiography; elektrokardiografie; Sex Characteristics; prospektivní studie; Male; Prospective Studies; Young Adult; pohlavní dimorfismus; komorová tachykardie; lidé středního věku; mužské pohlaví; Middle Aged; Humans